Three New Species of Perlesta (Plecoptera: Perlidae) from Eastern North America and Notes on New State Records - Kondratieff, Boris C. (Illiesia, 2006)
Three new species of the Nearctic Perlidae genus Perlesta are described from North Carolina and Virginia, USA. Perlesta leathermani sp. n. is described from Hoke/Moore County, North Carolina, P. bjostadi, sp. n. from the Harnett/Cumberland Co., North Carolina, and P. cranshawi sp. n. is described from Sussex Co., Virginia. The adult male, adult female, and egg are describedand illustrated for P. leathermani and P. cranshawi, and the adult male and adult female for P. bjostadi. Three new state records for North Carolina are also reported, P. puttmanni Kondratieff and Kirchner, P. roblei Kondratieff and Kirchner and Perlinella zwicki Kondratieff, Kirchner, and Stewart.
Keywords: insekti; Plecoptera; vrbnice